The Effect of Talent Management and Teamwork on Employee Performance Mediated by Employee Retention at Regional Office II of PT. Perkebunan Nusantara IV Medan - Murdhiyati Hilma Purba; Prihatin Lumban Raja; Elisabet Siahaan (Indonesian Journal Publisher, 2026)
The development of human resource management in the era of globalization demands that companies optimize employee performance through effective and sustainable strategies. This study aims to analyze the influence of talent management and teamwork on employee performance, with employee retention as a mediating variable, at Regional Office II of PT. Perkebunan Nusantara IV Medan. Using a quantitative associative approach with saturated sampling, all 134 employees served as respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). Results show that talent management and teamwork have a positive and significant effect on both employee performance and employee retention. Employee retention positively and significantly affects employee performance. Indirect effect testing confirmed that employee retention significantly mediates the relationship between talent management and teamwork with employee performance (partial mediation). These findings indicate that effective talent management, solid teamwork, and appropriate employee retention strategies can optimally enhance employee performance.